“Co-production Compass” (COCO): An Analytical Framework for Monitoring Patient Preferences in Co-production of Healthcare Services in Mental Health Settings - Graffigna, Guendalina; Barello, Serena; Palamenghi, Lorenzo; Lucchi, Fabio (Frontiers in Medicine, 2020)
Background. Engaging patients in raising their voices to advocate for their priorities being taken into account is today acknowledged as essential to improve research and decision making in healthcare. In this study we describe the process of development and first implementation of a new assessment framework for monitoring patient preferences collection in co-production of healthcare services within the scope of a national-based project (namely, Recovery.Net) in the mental health field. Method. We conducted 1) a narrative scan of relevant scientific literature on patient engagement in service co-production and 2) qualitative analysis of five subsequent workshops involving – in total – 144 expert stakeholders (i.e. expert patients; doctors; nurses; psychologists; healthcare managers…). Data analysis involved three phases: identifying the themes, developing a framework and confirming the framework. We coded and organized the data, and abstracted, illustrated, described and explored the emergent themes using thematic analysis. At the same time, content analysis was conducted to retrieve concepts and insights from relevant literature about health services co-production to integrate and extend the emergent conceptual framework. The framework was finally reviewed by the research partners belonging to the study project and preliminary implemented. Results. According to the results of both the literature scan and the participatory workshops, the COCO evaluation framework for monitoring patient preferences collection when coproducing medical pathways was drafted. The framework comprised of 3 organizing themes, corresponding to the 3 code clusters, which emerged from both the stakeholders’ workshop data and relevant scientific literature: “the need for shared and practice-oriented evaluation standards”; “the quest for a multi-dominion approach”; “the need for a multi-stakeholder evaluation”. These themes were interconnected and formed a conceptual framework to measure the phenomenon of meaningful patient involvement in healthcare co-production. This framework was endorsed by the research partners of the project and preliminary applied in a mental health setting. Conclusion. The COCO Framework provides guidance on aspects of co-production in healthcare to address for meaningful patient involvement in giving their inputs for more effective service and drug development processes. It could be particularly useful when monitoring patient‐researcher partnerships initiatives.